(untitled) (Revista Brasileira Multidisciplinar, 2013)
The sociologist Norbert Elias (1897-1990) is considered one of the most influential intellectuals of contemporaneity. His work is one of the conceptual windows that we intend to open in the studies of our research group. Considering that the basic task of research in the humanities is to make the social processes more accessible to the understanding of individuals within the social webs in which they are inserted, this paper aims to explore some interrelated concepts proposed by Elias in which he notes the changing patterns of interdependence between individuals and society and the impact of these standards within social groups. Therefore, the methodological procedure was the literature review. As a result of our study we present some key elements of the author’s thought, namely, configuration, interdependence, game, power and movement. To conclude, we believe that such elements, applied to educational issues, allow to expand the understanding of school as well as other educational institutions. So, after exploring these concepts, we tried to link them to the field of education, understanding that they may be a source of great theoretical value to provoke reflection and broaden the understanding of the functioning of educational institutions, especially about school. And because, from a broad perspective of social macro relations, we believe that to study school is also to study the problems of society. The studies of Elias allow us to look at school not as if we took a picture and analyzed it as a static institution, paralyzed in an instant, but as a social dynamic, flexible institution built and deconstructed permanently by the movement of the interrelationship between people who are part of it.